LEVERAGE EFFECT FORECAST FOR THE YEAR 2014 THROUGH THE MOVING AVERAGE METHOD - HADA TEODOR; DUMITRESCU DANIELA IONELA; CIOCA IONELA CORNELIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
It is very important for the proper development of various financial and economic activities to be an achievable goal. This can be determined by a forecast of a phenomenon in order to know where they could hover value. This paper is structured in three parts. The first part highlights the theoretical aspects of using the moving average method for determining the prognosis of a given phenomenon. The second part presents in detail the steps to follow within the moving average method. The phenomenon analyzed in this study is the leverage effect. We examine each step of the process, which will ultimately lead to a more precise forecast for the leverage effect. Each stage of the procedure is analyzed, which will lead in the end to a most accurate prognosis of the leverage effect. At the end of this paper, findings of practically using the moving average method, for establishing the forecast and its subsequent interpretations, will be presented.